Genomic Surveillance of Ceftriaxone-Resistant Escherichia coli in Western New York Suggests the Extended-Spectrum β-Lactamase blaCTX-M-27 Is Emerging on Distinct Plasmids in ST38 - Mostafa, Heba H.; Cameron, Andrew; Taffner, Samantha M.; Wang, Jun; Malek, Adel; Dumyati, Ghinwa; Hardy, Dwight J.; Pecora, Nicole D. (Frontiers in Microbiology, 2020)
Extended-spectrum β-lactamase (ESBL)-producing Enterobacteriaceae pose significant treatment and infection prevention challenges. E. coli sequence type (ST)131 associated with the blaCTX-M-15 gene has been the dominant lineage of ESBL-producing E. coli in the US and worldwide. In this study, our objective was to determine the β-lactamase profile, means of dissemination, prevalence, and the clonal identity of ESBL-producing E. coli in our region of Western New York. Whole-genome SNP-based phylogenomics was used to assess 89 ceftriaxone-resistant (CTR) E. coli. Isolates were collected from both inpatients and outpatients and from urine and sterile-sites over a 2 month period in 2017 or throughout the year, respectively. ST131 was the predominant ST (46.0%), followed by ST38 (15.7%). The blaCTX-M-15 gene was commonly found in 53.7% of ST131 isolates, whereas the blaCTX-M-27 gene was found in 26.8% of ST131, though was significantly associated with ST38, and was found in 71.4% of those strains. When compared to ST131, ST38 E. coli exhibited increased frequency of resistance to nitrofurantoin, and decreased frequency of resistance to ciprofloxacin and ampicillin-sulbactam. Using Nanopore long-read sequencing technology, an analysis of the ESBL genetic context showed that the blaCTX-M-15 gene was chromosomal in 68.2% of ST131, whereas the blaCTX-M-27 gene was plasmid-borne in all ST131 and 90% of ST38 isolates. Notably, the blaCTX-M-27 gene in ST38 resided on highly-related (99.0-100.0% identity, 65.0-98.0% query coverage) conjugative IncF plasmids of distinct pMLSTs from those in ST131. Furthermore, ST131 and ST38 were found to harbor different antibiotic resistance gene and virulence factor profiles. These findings raise the possibility of an emerging ESBL-producing E. coli lineage in our region.